Penetrating abdominal injury and peritonitis: A rare case of birth Injury - Patankar Shreeprasad; Patankar Shilpa (Wolters Kluwer Medknow Publications, 2008)
The incidence of birth injuries has decreased considerably because of the identification of risk factors at an earlier stage and taking the decision for caesarian section (LSCS) at proper time. Fractures, nerve palsies and central nervous system injuries comprise the majority of "birth injuries." In this study, we report a newborn that had a birth injury during LSCS. The baby sustained a penetrating abdominal injury by the knife of the surgeon, while performing LSCS. The bowel was injured at two sites, proximal jejunum and descending colon. The baby developed meconeum spillage and peritonitis. Exploratory laprotomy was done and the injuries were identified. The injured portions were resected and bowel continuity was reestablished. The baby had an uneventful recovery.